2022
DOI: 10.1017/exp.2022.26
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and content of televised UK gambling advertising during the men’s 2020 Euro soccer tournament

Abstract: Gambling marketing is frequently visible in the United Kingdom, especially around the national sport, soccer. Previous research has documented the frequency with which gambling marketing logos can be seen in domestic club soccer, and also the frequency of television advertising around international tournaments. The present research investigates the frequency and content of television advertising during the men’s 2020 Euro soccer tournament, a high-profile tournament shown since the industry’s voluntary “whistl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Of gambling advertising shown on TV, a significant focus has been international and club men's football (Newall et al, 2022;Sharman et al, 2023;Torrance, Heath, Andrade, et al, 2023). Although this high frequency of advertising in men's football has led to some industry self-regulation, one recent analysis suggested that this "whistle-to-whistle ban" only reduced the incidence of TV adverts by 43% (McGrane et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Of gambling advertising shown on TV, a significant focus has been international and club men's football (Newall et al, 2022;Sharman et al, 2023;Torrance, Heath, Andrade, et al, 2023). Although this high frequency of advertising in men's football has led to some industry self-regulation, one recent analysis suggested that this "whistle-to-whistle ban" only reduced the incidence of TV adverts by 43% (McGrane et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable attention has been paid to the role of marketing in the 'gamblification' of football and its potential negative impacts upon public health (Lopez-Gonzalez & Griffiths, 2018;McGee, 2020;van Schalkwyk et al, 2021). Gambling marketing is often shown during commercial breaks in televised football games (Newall, Ferreira, Sharman, & Payne, 2022;Newall, Thobhani, Walasek, & Meyer, 2019) and via social media (Houghton, McNeil, Hogg, & Moss, 2019;Houghton & Moss, 2022). However, the top two men's professional leagues, the English Premier League (EPL) and Championship, also have gambling marketing embedded within the game via shirt sponsorship and pitch-side hoardings (Bunn et al, 2019;Cassidy & Ovenden, 2017;Djohari, Weston, Cassidy, & Kulas-Reid, 2021;Purves, Critchlow, Morgan, Stead, & Dobbie, 2020;Sharman, Ferreira, & Newall, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Second, a selfregulatory "whistle-to-whistle ban" has removed any TV advertising during live sport since 2018, but only covering the interval from 5-minutes before to 5-minutes after the relevant game. This means that between 4.5 (Newall, Ferreira, et al, 2022) and 5.2 adverts (Sharman et al, 2023) were shown across the entire broadcasts of televised men's international soccer tournaments on average. Third, in 2023 the top flight of men's professional soccer, the English Premier League, agreed to prevent gambling companies from being front-of-shirt sponsors from August 2026 onwards.…”
mentioning
confidence: 98%
“…International research has found that gambling advertising tends to include certain specific themes, such as the promotion of "free bets" and other financial inducements (Di Censo et al, 2023;Hing et al, 2018;Killick & Griffiths, 2022;Lopez-Gonzalez et al, 2018). Gambling advertising has become so embedded in the UK that some adverts (commercials) are shown just to inform viewers about the potential harms of gambling, and these "safer gambling" adverts have been shown by both gambling operators and by independent charities (Newall, Ferreira, et al, 2022;Sharman et al, 2023). While widespread gambling advertising is relatively recent in the US and Canada (Grubbs & Kraus, 2023;Wheaton et al, 2024), it has been established for longer in Australia and various European jurisdictions (Hing et al, 2023), which has led to some countries such as Spain and Belgium now imposing restrictions (De Jans et al, 2024;Ministerio de la Presidencia, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation